Analysis of the accuracy of a dynamic navigation system when performing dental implant surgery with transcrestal sinus floor elevation: A pilot study - Bin-Zhang Wu; Fei-Fei Ma; Feng Sun (Elsevier, 2023)
Background/purpose: The success of transcrestal sinus floor elevation (TSFE) is primarily reliant upon the experience of the surgeon owing to the limited operative visibility. To evaluate the accuracy associated with the use of a dynamic navigation system when conducting posterior maxilla implant surgery with TSFE. Materials and methods: Twenty-eight implants were placed in 28 patients requiring implantation in the posterior maxilla via a TSFE approach. The drills were used to access the planned position (within 1 mm of the bottom of the maxillary sinus floor) under dynamic navigation system. TSFE was then accomplished using osteotomes and a piezoelectric device. Lastly, the implant was inserted under the dynamic navigation. Three effective deviations between planned and actual implant placement were then measured including angular deviation (AD, degrees), entry point horizontal deviation (EPHD, mm), and apical point horizontal deviation (APHD, mm). Results: The AD, EPHD, and APHD between the planned and actual implant placement were 3.656 ± 1.665°, 1.073 ± 0.686 mm, and 1.086 ± 0.667 mm, respectively. Premolar site AD values were less than those for molar sites (P = 0.004). No significant differences in these outcomes were observed in different surgeons. Obvious sinus perforation was not detected by immediate postoperative cone beam computed tomography imaging. Conclusion: The accuracy associated with using a dynamic navigation system when conducting posterior maxilla implant surgery via a TSFE approach using piezoelectric devices was comparable. This technique thus achieved appropriate interventional precision and safety while decreasing the morbidity associated with the TSFE approach.